Cost-efficient analysis of a portable low field magnetic resonance imaging system for prostate cancer diagnosis - Sze, Christina; Cheema, Zaid; Laviana, Aaron; Margolis, Daniel; Costa, Daniel N.; Satya, Poorvi; Nacev, Aleksander; Kumar, Dinesh; Venkataraman, Srirama S.; Chughtai, Bilal (Frontiers in Urology, 2022)
PURPOSE: Magnetic resonance imaging (MRI)-guided procedures are typically performed under high magnetic field strengths (1.5-3 Tesla) and are expensive. Recently, technological progress has led to MRIs that are low-cost but similarly high performing despite lower field strengths (58-74mT). Our purpose was to evaluate the cost-efficiency of implementing a low-field MRI for targeted prostate cancer biopsy. MATERIALS AND METHODS: We utilized time-driven activity-based costing (TDABC) to establish the overall costs based on cost rates and total times for every step. Thorough literature searches and consultations with two board certified radiologists, the process maps were created, and the duration of each step was determined by experience and previously published data. A sensitivity cost analysis was also performed to create several cost scenarios for the low-field MRI system. RESULTS: Total procedure times, performed under moderate sedation, were 61±14.5 mins and 57±23 mins for transperineal targeted biopsy (TPB) with low-field MRI and in-bore MRI-guided transrectal biopsy (IB-TBx) with high-field MRI. In the low-field MRI pathway, 61% of intra-operative time was spent on patient preparation and performing the prebiopsy MRI, however, this step did not require a urologist or radiologist expertise, subsequently keeping costs lower. A sensitivity analysis of the low-field MRI cost at 5% to 50% (in 5% increments) of a high-field MRI produced a difference from $888.13 to $879.18 favoring the lower-field system, respectively. CONCLUSIONS: A portable, low field, office-based MRI system offers a cost-efficient alternative to the high-field MRI. Further studies assessing cost effectiveness while taking into consideration sampling accuracy are needed.